A bridged‐switch energy‐efficient switching scheme for SAR ADCs with 2× input range - Bin Tang; Yunfeng Hu; QingMing Huang; Chaoyi Chen; Lexing Hu; Bin Li; Zhaohui Wu (Electronics Letters, 2024)
Abstract In recent years, successive approximation register (SAR) analogue‐to‐digital converters (ADCs) have been widely applied in Internet of Things (IoT) sensor devices. To reduce the power consumption of ADCs, a bridged‐switch energy‐efficient switching scheme for SAR ADCs with a 2× input range is proposed. Due to the use of top‐plate sampling, overall shift and bridged switch, the energy consumption of the first three comparisons and reset is zero, meanwhile the energy consumption of the fifth comparison is greatly reduced. The proposed switching scheme has an average energy consumption of 13.084CVref2, which reduces the switching energy by 99.04% compared to the conventional switching scheme. The proposed switching scheme can achieve a 2× input range with the same supply voltage, effectively reducing ADC power consumption and making it more suitable for IoT applications.